(untitled) (Revista de Crítica Literaria Latinoamericana, 2025)
The essays of Lienhard document the connection between Huaman Poma and J.M. Arguedas since the 1970s. They explore the idea of narrative subversion in the words, images, and symbols of the Andean cultural system. Lienhard, along with other Americanists, has gathered critical information and hypotheses about indigenous subalternity and literary writing. His approach distinguishes between hybrid genres of authors who cultivated orality and identified expressions and poetic figures in native languages that enhance the narrative strength of Amerin- dian voices. This paper analyzes some moments of his interpretative operation, not so much on the corpus of subversive literature in the Andes, focusing on the cultural exemplarity of Poma and Arguedas for their language, cosmological codes, and other contributions.